Integrative Study between Data Analysis and Shura Principles in Islamic Education Institutions - Nurhana Fakhriyah Imtinan; Abdurrozaq Abdurrozaq; Muhammad Thohir; Sahudi Sahudi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to examine the integration of data-driven approaches with the principle of shura in Islamic education management using a Systematic Literature Review (SLR) based on the PRISMA 2020 protocol. A total of 27 selected articles from reputable databases such as Scopus, Web of Science, and SINTA (2020–2025) were analyzed. The findings indicate a significant shift from administrative digitalization toward advanced data analytics and intelligent algorithms in decision-making processes. However, the dominance of technological approaches risks neglecting ethical, spiritual, and value-based dimensions inherent in Islamic education. Therefore, this study emphasizes the integration of Islamic epistemology, including bayani, burhani, and irfani, in decision-making. The concept of shura acts as a collective validation mechanism for data analysis results, ensuring that decisions are not purely algorithmic. This study proposes the Data-Driven Shura (DDS) model as an integrative framework combining data analytics with Islamic values to support holistic decision-making. The contribution lies in bridging modern technology with Islamic ethical principles in educational management.